Tháng Tư 19, 2024

Tìm \(x\) biết: \({\left( {x + 1} \right)^3} – {\left( {x – 1} \right)^3} – 6{\left( {x – 1} \right)^2} = – 10\)

Tìm \(x\) biết: \({\left( {x + 1} \right)^3} – {\left( {x – 1} \right)^3} – 6{\left( {x – 1} \right)^2} = – 10\)

A. \( -\frac{{ 1}}{2}\)

B. \( \frac{{ 1}}{2}\)

C. \( -2\)

D. \( 2\)

Hướng dẫn Chọn đáp án là: A

Lời giải chi tiết:

Hướng dẫn giải chi tiết

\(\begin{array}{l}{\left( {x + 1} \right)^3} – {\left( {x – 1} \right)^3} – 6{\left( {x – 1} \right)^2} = – 10\\{x^3} + 3{x^2} + 3x + 1 – \left( {{x^3} – 3{x^2} + 3x – 1} \right) – 6\left( {{x^2} – 2x + 1} \right) = – 10\\{x^3} + 3{x^2} + 3x + 1 – {x^3} + 3{x^2} – 3x + 1 – 6{x^2} + 12x – 6 = – 10\\12x – 4 = – 10\\12x = – 10 + 4\\12x = – 6\\x = -\frac{{ 1}}{2}\end{array}\)